Smartmentality: The Smart City as Disciplinary Strategy - Vanolo, Alberto (Urban studies (Edinburgh, Scotland), 2014)
The paper analyses the concept of the smart city in critical perspective, focusing on the power/knowledge implications for the contemporary city. On the one hand, smart city policies support new ways of imagining, organising and managing the city and its flows; on the other, they impress a new moral order on the city by introducing specific technical parameters in order to distinguish between the 'good' and 'bad' city. The smart city discourse may therefore be a powerful tool for the production of docile subjects and mechanisms of political legitimisation. The paper is largely based on theoretical reflections and uses smart city politics in Italy as a case study. The paper analyses how the smart city discourse proposed by the European Union has been reclassified to produce new visions of the 'good city' and the role of private actors and citizens in the management of urban development.